2023
DOI: 10.1038/s41598-023-43735-1
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering for enhanced optical and photocatalytic properties of ZnS nanoparticles synthesized by hydrothermal method

E. Muhammed Jubeer,
M. Aslam Manthrammel,
P. A. Subha
et al.

Abstract: Defect engineering is a promising method for improving light harvesting in photocatalytic materials like Zinc sulphide (ZnS). By altering the S/Zn molar ratio during hydrothermal processes, Zn and S defects are successfully introduced into the ZnS crystal. The band structures can be modified by adding defects to the crystal structure of ZnS samples. During the treatment process, defects are formed on the surface. XRD and Raman studies are used for the confirmation of the crystallinity and phase formation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…2 A-D. Based on the XPS analysis of Fig. 2 , confirm the elements and oxidation state of the elements such as Zn 2p (Zn 2+ ), S 2p (2 - ), C 1 s (4 + ) and N 1 s (3 - ) [ 27 ]. The peak separation of the peaks at 1022.5 eV and 1045.9 eV in Zn 2p spectrum ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…2 A-D. Based on the XPS analysis of Fig. 2 , confirm the elements and oxidation state of the elements such as Zn 2p (Zn 2+ ), S 2p (2 - ), C 1 s (4 + ) and N 1 s (3 - ) [ 27 ]. The peak separation of the peaks at 1022.5 eV and 1045.9 eV in Zn 2p spectrum ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The peak separation of the peaks at 1022.5 eV and 1045.9 eV in Zn 2p spectrum ( Fig. 2 A) and which was originated from the Zn 2p 3/2 and Zn 2p 1/2 of ZnS [ [27] , [28] ]. In other hand, the S 2p could be deconvoluted into the peaks at 162.5 eV and 163.2 eV, assigned to S 2p 3/2 and S 2p 1/2 of ZnS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that when the energy of the radiation exceeds the band gap width of ZnS, matched holes (h + ) grow in the valence band (VB), creating a “electron hole” pair. In contrast, excited electrons in the valence band (VB) can jump into the conduction band (CB) 44 . According to Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…The abovementioned processes demonstrate that photocatalytic degradation is possible when soluble oxygen and H 2 O are present. There have been other reports of similar methods for the photocatalytic destruction of dyes 44 . As a result, ZnS nanoparticles have the potential to purify them, which causes photocatalysis to destroy indigo carmine dye.…”
Section: Resultsmentioning
confidence: 99%